(8x+3)+(3x-6)=180

Simple and best practice solution for (8x+3)+(3x-6)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8x+3)+(3x-6)=180 equation:


Simplifying
(8x + 3) + (3x + -6) = 180

Reorder the terms:
(3 + 8x) + (3x + -6) = 180

Remove parenthesis around (3 + 8x)
3 + 8x + (3x + -6) = 180

Reorder the terms:
3 + 8x + (-6 + 3x) = 180

Remove parenthesis around (-6 + 3x)
3 + 8x + -6 + 3x = 180

Reorder the terms:
3 + -6 + 8x + 3x = 180

Combine like terms: 3 + -6 = -3
-3 + 8x + 3x = 180

Combine like terms: 8x + 3x = 11x
-3 + 11x = 180

Solving
-3 + 11x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 11x = 180 + 3

Combine like terms: -3 + 3 = 0
0 + 11x = 180 + 3
11x = 180 + 3

Combine like terms: 180 + 3 = 183
11x = 183

Divide each side by '11'.
x = 16.63636364

Simplifying
x = 16.63636364

See similar equations:

| -12-6n=6+3n | | -0.6x-0.2=0.5x+0.02 | | 6378.1-2981.1=x | | 4-7p=-15p | | 5c=45 | | 1+5m=-3+6m | | 13p=44-9p | | 7+x=16 | | 50=7(x+3)+1 | | 2+3-2p+1=7p-8p | | 0.6x-0.2=0.5x+0.2 | | 24x^3-10x^2-4x=0 | | 6x-7=-4x+3 | | h=0 | | -8(2-x)-(x-5)=8 | | 5(9+2x)=240 | | 11y-(2-4y)=13+2(y-1) | | 2v+49=-7-5v | | 0.6x-0.2=0.5x-0.2 | | 5x-8x=8x | | 24x^3-10x^2-24x^3=0 | | 8x-10=5x+8 | | 4(x+2)-(2x-7)=0 | | -4-6a=4-2a-5a | | 26-(3x-10)=16 | | -8(2-x)-(x-5)=31 | | x+2/3=3x-5/6 | | 23+y=16 | | 6k+7=7k | | 13c+20=2c-35 | | 9+3w=7+9w | | 12+5s=-78 |

Equations solver categories